Efficacy of Various Hypoglycemic Agents in the Treatment of Patients With Nonalcoholic Liver Disease With or Without Diabetes： A Network Meta-Analysis - Lian, Jingxuan; Fu, Jianfang (Frontiers in Endocrinology, 2021)
[Abstract] Objective: To comprehensively evaluate and compare the therapeutic effects of various hypoglycemic agents in NAFLD patients with or without diabetes. Methods: All literature from the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, and Clinical Trials was searched, and the language was limited to English. Two reviewers independently assessed study eligibility, continuous data extraction, and independent assessment of bias risk. Our primary outcomes were alanine aminotransferase (ALT), aspartate aminotransferase (AST) and triglyceride levels, while our secondary outcomes were high-density lipoprotein (HDL) and low-density lipoprotein (LDL) levels, body weight, BMI, and fasting glucose and glycosylated hemoglobin (HbA1c) levels. Results: The review identified 20 eligible trials that met the inclusion criteria. We found that, compared to other drugs, thiazolidinediones, especially pioglitazone, had a greater effect on the levels of ALT (-8.01 (95% CI -14.3 to 2.02)) and AST (-5.0 (95% CI -9.21 to -1,22)) and other biological indicators, but they were also associated with an increased risk of weight gain (3.62 (95% CI 2.25 to 4.99) and increased BMI (0.59 (95% Cl -0.13 to 1.29). GLP1 RAs and metformin also had better therapeutic effects than other drugs as measured by the levels of ALT (liraglutide: -9.36 (95% Cl -18 to -0.34), metformin: -2.84 (95% CI -11.09 to 5.28)) and AST (liraglutide: -5.14 (95% CI -10.69 to 0.37), metformin: -2.39 (95% CI -7.55, 2.49)) and other biological indicators. Conclusion: Despite the significant risk of weight gain, thiazolidinediones, especially pioglitazone, are beneficial in normalizing liver and glucose metabolism in NAFLD patients. In clinical practice, we believe that GLP1 RAs such as liraglutide and exenatide or metformin can be used in combination to offset the risk of weight gain associated with thiazolidinediones. However, long-term studies are still needed to verify the efficacy and safety of individual hypoglycemic agents.